Implementasi Pendekatan Integrasi dan Interkoneksi Ilmu Interdisipliner pada dalam Kajian Manajemen Pendidikan Islam - Febriyenti, Dini; Rizandi, Hidayat; Saputra, Roni; Ardimen, Ardimen (Fakultas Tarbiyah IAI Nasional Laa Roiba, 2024)
This study aims to explain the Implementation of the Integration and Interconnection Approach of Interdisciplinary Science in Islamic Education Management Studies. This research uses qualitative methods with data collection techniques through library research which involves collecting information and data from various sources found in libraries such as reference books, research relevant previous studies, articles, related notes and including journals related to the topic to be completed. The development of information and communication technology has influenced the development of science. Keywords : Integration-interconnection, Interdisciplinarity, Management of Islamic Education